The Correlation between EFL Learners' Self-directed and their Level of Productive Skills (مجلة ديالى للبحوث الانسانية, 2025)
The ability to communicate effectively is one of the key goals of learning the English language. Effective communication allows for the exchange of information, ideas, and feelings as well as the expression of opinions, negotiation of themes, and evocation of emotions. The ability to communicate is essential to acquiring the English language. It gives students the chance to practice speaking, pick up new words, and understand different cultures. However, gaining productive skills in a classroom setting can be greatly aided by learning English. These goals may be related to learners' seeking mastery of new skills or gaining better performance and judgments in comparison with others. Accordingly, the current study is conducted to explore the correlation of EFL learners' level of self-directed learning (SDL) with their productive skills. The population of the study represents EFL students at the departments of English of the Iraqi colleges of education, except for the Kurdistan region, for the academic year (2022-2023). The sample, on the other hand, is purposive and includes 310 EFL students selected from the 3rd year students of the English Departments of the College of Education, Ibn Rushd for Human Sciences/ University of Baghdad (110 students), College of Education/ University of Diyala (107 students), and College of Education/ University of Tikrit (83 students). The total number of 3rd year students in the departments included is 995 students from whom a percentage of 30% is relied on in selecting the sample.The research design of the current study is a correlational in nature through which two instruments are used, after being approved and validated by a jury of experts. These are:• a 28-item questionnaire to assess students' Self-directed learning,• a productive skills test.   The results obtained reveal that there are positive significant correlations between EFL learners' SDL and productive skills.